Bilateral Sensorineural Hearing Loss and Polyneuropathy in a Patient with Sweet's Syndrome. (6th December 2015) - Cala, Cather M.; Kole, Lauren; Sami, Naveed
Abstract : Sweet's syndrome is an inflammatory systemic disease which has been associated with various underlying causes. The disease can involve multiple areas of the body including the skin and neurological system. There have been only two cases which have described otological involvement. This report presents a patient who developed loss of hearing secondary to Sweet's syndrome after developing cutaneous involvement along with peripheral neuropathy. Despite the patient's skin and neuropathy noticing improvement with intravenous immunoglobulin and azathioprine, he required bilateral cochlear implants for partial recovery of his hearing loss. This case highlights the need to recognize Sweet's syndrome as a complicated disease process where the role of otolaryngologists is important in the multidisciplinary coordination of care in both diagnosis and treatment.